Examination of upper respiratory tracts of Siirt-coloured mohair goats by scanning electron microscopy before and after plastination - Guzel, Baris Can; Baygeldi, Saime Betul; Ozkan, Zait Ender (Wiley, 2024)
Present study was conducted to determine the changes in the surface structure of the upper respiratory tract of Siirt-coloured mohair goats by the silicone plastination method. Accordingly, the heads of 10 Siirt-coloured mohair goats procured from slaughterhouses were divided into two halves. Half of each head was plastinated. After macro-comparisons were made, the deformations of silicone plastination on the surface were examined by comparing the scanning electron microscope (SEM) findings of both upper respiratory tract tissue samples collected from plastinates and fresh material. When the data from scanning electron microscopy were analysed, cilia, cobblestone patterns, goblet cells and gland ducts on the epithelial surface were identified in areas on the upper respiratory tract. The SEM images of the plastinated tissues showed that the surface structures were degenerated due to the deformation of the surface epithelium. The plastination technique damaged the structures on the surface epithelium. Since the plastination technique and scanning electron microscopy have been studied together for the first time, we believe this would contribute to the scientific literature.
Keywords: goat; plastination; respiratory system; SEM